FINANCIAL CAPACITY AND DEFINITION METHODOLOGIES FOR ITS ASSESSMENT BY THE EXPERT METHOD (World Economics and Finance Bulletin, 2025)
This article, devoted to methodological approaches and practical implementation of financial potential and its impact on increasing state budget revenues, analyzes the methodology of financial potential using the analysis of budget indicators and the expert method. Attention is also paid to the influence of financial potential on the financing of social initiatives of the state. In conclusion, conclusions are given on increasing the prospects for the development of financial potential and increasing state budget revenues
Keywords: financial potential; analysis of budget indicators; social initiative